Los procesos cognitivos básicos y la comprensión lectora en los estudiantes de primer ciclo, paralelo “A” de la carrera de Economía de la Facultad Jurídica, Social y Administrativa de la Universidad Nacional de Loja, 2023-2024 - Rojas Pintado, Noelia Marisol (2024)
The aim of this curriculum integration study was to investigate the interaction between fundamental cognitive processes such as attention and memory and reading comprehension among first-cycle students enrolled in the Economics program, parallel "A," during the academic year 2023-2024. Utilizing a descriptive methodology with a quantitative, correlational, and cross-sectional approach, the research employed a non-experimental design. The d2 Attention Test, the memory subscale of the RIAS Test, and the Instrument for Assessing Reading Comprehension (ICLAU) were administered to a purposive non-probabilistic sample of 29 students. Data processing and analysis were conducted using the SPSS statistical software, including descriptive frequency analysis both globally and comparatively across variables. Key findings revealed that 72.41% of the students exhibited a low level of attention, with 65.52% demonstrating a medium level, and 24.14% a low level. Similarly, in terms of reading comprehension, 65.52% displayed a low level, and 24.14% a medium level. It was concluded that there exists a moderate positive correlation between the variables under study, with Kendall's Tau-b values of 0.198 for attention and 0.190 for memory. Consequently, based on the research findings, the null hypothesis was rejected, while the alternative hypothesis was accepted.